Pattern of congenital eye anomalies in children: A study from rural tertiary care hospital - Jain, Rakhi; Pathania, Vishal; Saini, Nishtha (Asian Journal of Medical Sciences, 2022)
Background: Congenital eye anomalies are an important cause of childhood blindness. Worldwide, there are a lot of variations in the spectrum of congenital eye anomalies. The key to preventing childhood blindness is early detection and intervention of the congenital eye anomalies. Aims and Objectives: This study aims to describe the type and frequency of congenital eye anomalies in children. Materials and Methods: This cross-sectional study was done on children attending pediatric OPD and the newborn babies born in the hospital in the period of 1 year from June 2019 to May 2020. They were screened for any ocular abnormality and then detailed ocular examination was done by the ophthalmologist. The data were collected for demographic characteristics, clinical diagnosis, age of presentation of anomaly, laterality, involvement of one or both eye, and type of anomaly. Variables were expressed as proportions or percentages. Results: A total of 32,858 children were screened for ocular abnormalities. Out of these, 1571 (0.047%) children had ocular abnormalities. Among them, 1011 (64.35%) presented in the 1st year of life, 381 (24.25%) in the 2nd year of life, and the remaining 179 (11.4%) were diagnosed after 2 years of life. Among various anomalies, congenital nasolacrimal duct obstruction was the most common anomaly (65%) followed by coloboma of iris and choroid (13.8%). Congenital ectropion and anopthalmos were found in five and three children, respectively. Conclusion: The most common anomaly was congenital nasolacrimal duct blockage followed by coloboma of iris, choroid, and cataract. Early detection and intervention of the congenital eye anomalies is necessary to prevent blindness.